CORNEAL TOPOGRAPHICAL AND BIOMECHANICAL INDICES IN MOTHERS OF CHILDREN WITH DOWN’S SYNDROME IN A TERTIARY CARE HOSPITAL OF PAKISTAN (The Research of Medical Science Review, 2025)
Objective: To investigate corneal topographical and biomechanical parameters in mothers of children diagnosed with Down’s syndrome (DS), and to compare them with mothers of children without Down’s syndrome, in a tertiary care hospital in Pakistan. Study design: A comparative cross-sectional study.Place and Duration of study: Armed Forces Institute of Ophthalmology, Rawalpindi, Pakistan, from June 2024 to November 2024Methodology: A comparative analysis was carried out, 188 eyes of 94 patients were studied, forty-seven in Group-A (mothers of Down’s syndrome children) and forty-seven in Group-B (mothers of normal children). In this study, the corneal topographical and biomechanical parameters of mothers of children diagnosed with Down’s syndrome were studied and compared to their age matched counterparts.Results: The participants average age was 35.8 years in Group-A and 33 years in Group-B. Statistically significant differences were observed between group means for flat simulated keratometry K1 (p value 0.00), steep simulated keratometry K2 (p value 0.00), K maximum (p value 0.024), Belin Ambrosio Enhanced Ectasia Display (p value 0.002) and Topographical biomechanical index (p value 0.02)Conclusion: Our findings reveal a higher prevalence of deranged keratoconus parameters in Group A than in Group B, pointing toward a milder, subclinical presentation of the condition.